Pengaruh Likuiditas dan Profitabilitas, terhadap Nilai Perusahaan Manufaktur Sub Sektor Kimia yang terdaftar di Bursa Efek Indonesia periode 2019-2021 - Agustina Waromi; Maria Wesso; Fenska Mbaubedari (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The research entitled The Effect of Liquidity and Profitability on the Value of Chemical Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The purpose of this study is to determine 1) the development of Liquidity and Profitability on company value, 2) to determine the partial effect of Liquidity and Profitability on company value, 3) to determine the simultaneous effect of liquidity and profitability on company value. This research is a quantitative research type. The sample used in the study was 12 chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Data collection techniques used documentation and literature studies. This study uses stock data of issuers included in the Chemical Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2021 period and analyzed using descriptive and inferential statistics using the Smart PLS 3.8 application. The results of descriptive statistics show that partial liquidity testing has a negative and insignificant effect on the value of chemical sub-sector manufacturing research on the Indonesia Stock Exchange in 2019-2021, marked with a significance value of 0.331, while partial results for profitability have a positive and significant effect on the value of chemical sub-sector manufacturing companies on the Indonesia Stock Exchange in 2019-2021, marked with a significance value of 0.037 and 0.000 below the alpha level used 5%. The results of simultaneous testing show that two variables that are carefully examined, namely liquidity and profitability, have a positive and significant effect on the value of the company, this is indicated by a t-value of 13.671 with a significance value of 0.000 below the alpha level used 5%. The coefficient of determination (R2) shows that the contribution of liquidity and profitability variables to the maintenance value of chemical sub-sector manufacturing is 59.2%, the remaining 40.8% is influenced by other variables not included in this research model. This research suggests that many manufacturing companies in the chemical subsector listed on the Indonesia Stock Exchange (IDX) performed poorly in 2019-2021, and therefore, they must further improve their performance.